(untitled) (The Journal of Interdisciplinary Human Studies, 2026)
This article gives a well-grounded account of the symbol of the cross in the Christian religion: its history, the legends concerning its origin, and the types of crosses. The valuable views of scholars on the symbol of the cross are studied comparatively, and the appearance of this emblem both in history and in the present day is presented in its symbolic expression.